2013
DOI: 10.3892/or.2013.2858
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the JAK-STAT3 pathway is associated with the growth of colorectal carcinoma cells

Abstract: Abstract. Excessive activation of inflammatory signaling pathways facilitates colorectal carcinoma (CRC) malignancy. Continuous activation of the Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathway plays a central role in the development and progression of CRC. With the intent to explore whether attenuation of the JAK-STAT3 signaling axis inhibits cancer cell proliferation or induces apoptosis, a sophisticated oncolytic adenoviral vector, AdCN305, carrying the SOCS3 gene was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…SOCS3 silencing has been shown to induce the phosphorylation of STAT3 and uncontrolled proliferation in myeloid leukemia cells (32). Overexpression of STAT3 suppressed the continuous activation of the JAK/STAT3 signaling pathway in colorectal carcinoma cells, inhibited cell growth, and induced apoptosis in vitro and in vivo (33). These findings confirm that the STAT3 signaling pathway is inhibited by SOCS3.…”
Section: Discussionsupporting
confidence: 68%
“…SOCS3 silencing has been shown to induce the phosphorylation of STAT3 and uncontrolled proliferation in myeloid leukemia cells (32). Overexpression of STAT3 suppressed the continuous activation of the JAK/STAT3 signaling pathway in colorectal carcinoma cells, inhibited cell growth, and induced apoptosis in vitro and in vivo (33). These findings confirm that the STAT3 signaling pathway is inhibited by SOCS3.…”
Section: Discussionsupporting
confidence: 68%
“…These results suggested that SOCS3 is critical to neovascularization and that reduction of SOCS3 expression in Vldlr −/− versus WT retinas may be secondary to up-regulation of Tnf / Tnfaip3 induced by c-fos . SOCS3 inhibits activation of STAT3 by binding to the kinase JAK and the IL-6 receptor (Wei et al, 2014), which induces the expression of VEGF (Wei et al, 2003). Consistently, we found that, in Vldlr −/− retinas, overexpression of Socs3 suppressed the increased VEGFA level by ∼45% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular stimulation could often induce alteration of intracellular redox status, which will affect conformation and function of signal molecules to regulate the signal transduction pathways 67 . It is well accepted that intracellular redox imbalance is involved in abnormal activation of some pathways that are closely related with CRC initiation and development, such as the Wnt/β-catenin signaling pathway, PI3K/AKT signaling pathway and the JAK/STAT signaling pathway 68 - 70 .…”
Section: The Relation Between Oxidative Stress and Crcmentioning
confidence: 99%